Bartter syndrome type III with glomerular dysplasia and chronic kidney disease: A case report - Liu, Jingqi; Zhang, Yudi; Wu, Xiaochuan; Li, Yongzhen (Frontiers in Pediatrics, 2023)
Background:Bartter syndrome (BS) type III is a rare autosomal recessive genetic disease. Its clinical features are polyuria, hypokalemia, hypochloremia, metabolic alkalosis, and hyperreninaemia, and a few of it can be complicated with chronic kidney disease. Case presentation:We report a 14-year-old boy with Bartter syndrome caused by a c.1792C>T (p.Q598*) mutation in the CLCNKB gene. He was a no deafness and full-term baby and he has renal dysplasia and chronic kidney disease (CKD), in addition, we summarized all cases of BS type III complicated with CKD. Conclusions:We reported a case of Bartter syndrome complicated with chronic kidney disease caused by a new mutation of CLCNKB. As we all know, it is usually BS type IV combined with chronic kidney disease, and BS type III can also combine with CKD. We don’t find BS type III with glomerular dysplasia in the literature. So renal damage in BS type III is not only FSGS, but also clinicians need to be aware of glomerular dysplasia.